Determining application rates of FYM and pressmud to improve soil health properties in salt degraded soils - M. L. Dotaniya; M. D. Meena; R. L. Choudhary; M. K. Meena; V. D. Meena; H. V. Singh; R. S. Jat; R. K. Doutaniya; Kuldeep Kumar; Harpreet Singh; P. K. Rai (PLoS ONE, 2025)
Improving food grain production by enhancing plant nutrient availability is critical for meeting future production. In this line, degraded soils may have the potential to meet the food demand of future population. However, the key challenge is excessive concentration of salts. It adversely mediates the soil fertility parameters, physical properties and soil enzymatic activities. Addition of organic substances, such as farm yard manure (FYM) and pressmud (PM), may improve soil health parameters. An incubation experiment was conducted with graded application of FYM (0, 2.5, 5 and 10 t/ha) and PM (0, 2.5, 5 and 10 t/ha) to monitor the nutrient release pattern of FYM and PM; and its effect on soil physico-chemical properties and soil enzymatic activities. The results showed that soil pH and EC were reduced after the one year incubation period. It was also observed that available plant nutrients like N, P, K, S and soil enzymatic activities reported highest in treatment FYM and PM (each applied 10 t/ha) over control. The findings of this study suggested that organic amendments can improve soil fertility, mitigate salt ion toxicity, and enhance food production potential, particularly in arid and semi-arid soils.